2011
DOI: 10.1158/1940-6207.capr-10-0340
|View full text |Cite|
|
Sign up to set email alerts
|

Gambogic Acid Inhibits STAT3 Phosphorylation through Activation of Protein Tyrosine Phosphatase SHP-1: Potential Role in Proliferation and Apoptosis

Abstract: The transcription factor, signal transducer and activator of transcription 3 (STAT3), is associated with proliferation, survival, and metastasis of cancer cells. We investigated whether gambogic acid (GA), a xanthone derived from the resin of traditional Chinese medicine, Gamboge hanburyi (mangosteen), can regulate the STAT3 pathway, leading to suppression of growth and sensitization of cancer cells. We found that GA induced apoptosis in human multiple myeloma cells that correlated with the inhibition of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 54 publications
0
26
0
1
Order By: Relevance
“…GA, the major active ingredient of gamboges secreted from the Garcinia hanburryi tree, has antitumor properties in solid tumors of various derivations in vitro and in vivo (27). The mechanisms of the anticancer activities of GA are complex and the most significant contributor has yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…GA, the major active ingredient of gamboges secreted from the Garcinia hanburryi tree, has antitumor properties in solid tumors of various derivations in vitro and in vivo (27). The mechanisms of the anticancer activities of GA are complex and the most significant contributor has yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Gambogic acid showed both growth arrest and apoptosis induction effects on Jurkat cells by significantly suppressing the expression of nucleophosmin, which indicated the fact that nucleophosmin and some nucleoporins might serve as new targets of gambogic acid (69). Gambogic acid inhibited tumor cell proliferation by blocking STAT3 activation which associated with proliferation, metastasis, and survival of cancer cells (70). The result of the in vitro research on K562 cells suggests that gambogic acid showed its anti-leukemia effects partially by suppressing the expression level of hERG channel in K562 cells, indicating that gambogic acid can be a promising antitumor agent against leukemia with a mechanism of inhibiting the hERG channel (71).…”
Section: Inhibition Of Proliferation and Induction Of Apoptosisrelatementioning
confidence: 93%
“…Prasad et al [3] found that GA induced MM cell apoptosis that correlated with inhibition of both constitutive and IL-6-induced STAT3 activation in a dose-and time-dependent manner. STAT3 suppression is mediated through the inhibition of activation of JAK1 and JAK2.…”
Section: Stat3 Inhibitionmentioning
confidence: 99%
“…Over the last decade, studies show that GA [3] , Curcumin [32] , Resveratrol [33] and Icaritin [28] have shown significant efficacy in blocking STAT3 activation and thereby inducing apoptosis in multiple myeloma cells. Prasad et al [3] found that GA induced MM cell apoptosis that correlated with inhibition of both constitutive and IL-6-induced STAT3 activation in a dose-and time-dependent manner.…”
Section: Stat3 Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation